1992
DOI: 10.1063/1.462495
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of the surface tension of a drop

Abstract: The curvature dependence of the liquid–vapor surface tension is described in the limit of small curvatures by Tolman’s length. Measurements of it, either experimentally or in a simulation, have not yet given a clear idea of its magnitude, even its sign is being debated. Previous attempts to relate Tolman’s length to a pressure tensor have led to ill-defined expressions. From an analysis of the pressure difference over the interface of a liquid drop, a pressure tensor expression is obtained for Tolman’s length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 21 publications
8
102
1
1
Order By: Relevance
“…(6) gives the same result for any pair of R l and R v in the bulk phase. Besides, Laplace equation [12] …”
Section: Some Equations For Cylindrical Vapour Bubblesmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) gives the same result for any pair of R l and R v in the bulk phase. Besides, Laplace equation [12] …”
Section: Some Equations For Cylindrical Vapour Bubblesmentioning
confidence: 99%
“…For cylindrical vapour bubbles, the Tolman equation (3) should be replaced by Tolman equation [12] γ…”
Section: Theoretical Basis and Calculation Schemementioning
confidence: 99%
“…Such an approach has been attempted before, 12,13 with limited success due to the difficulty of the calculation and the limited computational resources available at the time. Instead, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…͑6͒ below, [9][10][11] or were inconclusive. 12, 13 Moody and Attard 14 determined the Tolman length from simulations of a liquid near coexistence solvating a hard-wall cavity and found that the Tolman length was positive at low temperatures, changed sign at a certain temperature, and became increasingly negative as the temperature increased. It is not clear how the Tolman length for a solvated hard-wall cavity in a liquid near coexistence compares with that of a liquid drop surrounded by its vapor, though these authors give reasons why they ought to be the similar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation